Crime in the neighborhood a novel - Berne, Suzanne (New York : Henry Holt, 1998)
A seductive story of suspicion, fear and moral corruption, this is the tale of 10-year-old Marsha. Her life is in turmoil following the collapse of her parents' marriage, and the brutal murder of a local boy. When the shy bachelor from next door begins to take an interest in Marsha's mother, Marsha is drawn into a cruel spiral of events that quickly spins out of control. 'Immaculate and impressive' - "The Literary Review".
"An Owl book."
88650
Keywords: Crime -- Washington (D.C.) -- Fiction; Child witnesses -- Fiction; Washington Metropolitan Area -- Fiction